Konsep Dasar Pengembangan Kurikulum PAI - Kurniati Darwis; Fitriani; Riswandi Ardiansyah; Aminullah (CV. Creative Tugu Pena, 2024)
This research aims to determine the basic concepts of PAI curriculum development. This research focuses on three things: namely the meaning of PAI curriculum development, the objectives of PAI curriculum development, the components of PAI curriculum development, and the stages of PAI curriculum development. This research analyzes the basic concepts of PAI curriculum development. The research method used is qualitative research with a library research approach. The data collection technique used is to choose a topic and search for information from various sources (books, magazines, mass media, etc.). The data obtained were analyzed using the Miles and Huberman method. That is, we collect data, code it to simplify the analysis process, and draw conclusions. The research findings explain that the basic concept of PAI curriculum development is planning activities to create a better PAI curriculum. The objectives of developing the PAI curriculum are based on the national education objectives contained in Article 3 of Law Number 20 of 2003 concerning the National Education System (UU Sisdiknas). The components of PAI curriculum development are learning objectives, materials, learning methods, learning media, development, assessment or evaluation, and stakeholder involvement. Likewise with the PAI curriculum development orientation, namely, value development orientation, social demands orientation, workforce orientation, student orientation, and science and technology development orientation